Analysis Of Limited Face-To-Face Learning in Kindergarten Kuntum Bumi Rantauprapat Due to Covid-19 - Isyah Rahmini; Abdul Hakim; Maya Jannah (Budapest International Research and Critics University, 2022)
This study was conducted to identify and analyze the limited face-to-face learning at Kuntum Bumi Rantauprapat Kindergarten due to COVID-19. The research method used in writing this article is a normative juridical research method by reviewing the joint decree of 4 ministers No.440-771 Year 2021. Data collection techniques were obtained from journals, observations, documentation, and documents related to face-to-face learning analysis. Limited advances at Kuntum Bumi Rantauprapat Kindergarten. The results of this study are limited face-to-face learning at Kuntum Bumi Rantauprapat Kindergarten due to covid-19, namely, Kuntum Bumi Kindergarten implements applicable regulations such as asking for Dangen's approval using a statement signed by the student's parents using 6000 stamp duty. carry out complete vaccinations, continue to comply with Health protocols by providing hygiene facilities such as places for washing hands, soap and running water.